Thoracal Spinal Fusion In Tuberculous Spondylitis With Pulmonary Oedema And Thrombocytosis: A case report - Julius Daely, Pieter (Syntax Corporation Indonesia, 2025)
TB is caused by Mycobacterium tuberculosis (M. tb). Tuberculosis (TB) prevalence is increasing in developed nations and continuing to cause significant mortality in low and middle income countries. When M. tb disseminates to the vertebral column, it is called Pott’s disease or spinal TB. The frequency, symptoms, and severity of the disease range by the location of the spine and the region of the affected vertebrae. The delay in establishing diagnosis and management results in complications such as spinal cord compression and spinal deformity. Tuberculous spondylitis is the most dangerous form of musculoskeletal tuberculosis because it can cause bone destruction, deformity and paraplegia. The spread of tuberculosis infection will cause inflammation in paradiscs, and causes progressive bone destruction and then will make vertebral collapse and deformity arising shaped kyphosis (posterior angulation) called gibbus. The role of surgical debridement and fusion with TB is controversial, and good results may be obtained with either medical treatment or surgery. Surgery may be more appropriate when definite cord compression is documented or for complications such as abscess or sinus formation or spinal instability.